Two mutations within a feline mucopolysaccharidosis type VI colony cause three different clinical phenotypes. - Crawley, A C (1998)
Mucopolysaccharidosis type VI (MPS VI) is a lysosomal storage disease caused by a deficiency of N-acetylgalactosamine-4-sulfatase (4S). A feline MPS VI model used to demonstrate efficacy of enzyme replacement therapy is due to the homozygous presence of an L476P mutation in 4-sulfatase. An additional mutation, D520N, inherited independently from L476P and recently identified in the same family of cats, has resulted in three clinical phenotypes. L476P homozygotes exhibit dwarfism and facial dysmorphia due to epiphyseal dysplasia, abnormally low leukocyte 4S/betahexosaminidase ratios, dermatan sulfaturia, lysosomal inclusions in most tissues including chondrocytes, corneal clouding, degenerative joint disease, and abnormal leukocyte inclusions. Similarly, D520N/D520N and L476P/D520N cats have abnormally low leukocyte 4S/betahexosaminidase ratios, mild dermatan sulfaturia, lysosomal inclusions in some chondrocytes, and abnormal leukocyte inclusions. However, both have normal growth and appearance. In addition, L476P/D520N cats have a high incidence of degenerative joint disease. We conclude that L476P/D520N cats have a very mild MPS VI phenotype not previously described in MPS VI humans. The study of L476P/D520N and D520N/ D520N genotypes will improve understanding of genotype to phenotype correlations and the pathogenesis of skeletal dysplasia and joint disease in MPS VI, and will assist in development of therapies to prevent lysosomal storage in chondrocytes.